The geology of the diamondiferous inner shelf off Namaqualand between Stompneus Bay and White Point just north of the Buffels River - Woodborne, M W (Department of Geological Sciences, 2019)
This study describes the geology and late Quaternary history of the inner shelf just north of the Buffels River off Namaqualand. In this area the inner· shelf is only 2km to 3.5km wide. An "inner-shelf platform" slopes gently (1°) out to -40m. An "inner-shelf slope11 then grades relatively more steeply (2-3°) down from -40m to -75m where it is buried by a wedge of terrigenous sediment which lies at the foot of the inner-shelf slope. Precambrian bedrock is exposed over 70% of the inner shelf. Bedrock morphology, compiled from high-resolution seismic profiles, shows erosional features in the bedrock surface which indicate potentially diamondiferous areas. Gently sloping (1°) wave-abraded terraces occur at -14m to -lam, -22m to -28m, -33m to' -40m and -44m to -53m. Palaeo-channels of the Kwaganap and Kamma Rivers extend across the inner-shelf platform. Sonographs show that rugged bedrock with NNE-SSW- and NNW-SSE-trending strike-gullies (Acoustic Facies 1) occurs mostly at >30m depth and also around reefs at Stompneus Shoal and Penguin Rock. Low micro-relief bedrock with sediment-filled strike-gullies, also trending NNE-SSW and NNW-SSE (Acoustic Facies 2) , delineates the areal extent of -14m and -22m terraces. A deposit of boulders and cobbles interspersed with patches of gravelly sand (Acoustic Facies 3) occurs on the protected, landward side of Stompneus Shoal and Penguin Rock. This deposit may be associated with a lobate basal unit (shown in the seismic profiles) marking a -30m sea-level palaeo-beach within the deposit of sand north of Penguin Rock. Fine sand (Acoustic Facies 4), up to 7m thick, blankets the inner-shelf slope between Stompneus Bay and Twee Pad and extends onto the inner-shelf platform at Rob Eiland and Deurloop Bay. The sand thins progressively northwards and seismic profiles show that it extends seaward beneath the Holocene mud deposit (Acoustic Facies 5) which buries the inner-shelf slope below -75m. Evidence from this study implies that the 25m-30m thick wedge of sediment at the base of the inner-shelf slope consists. of seaward-thinning lenses of sand overlain by a thin (8-lOm) deposit of Holocene mud. The origin of the fine sand is attributed to wave-erosion of a late Pleistocene palaeo-dunefield immediately north of the Buffels River during the Flandrian transgression. In much of the study area (>70%) this reworking removed the overburden of dune sand originally covering the bedrock and the diamondiferous gravels. The upper 4m of the mudbelt shows two texturally different units and below this depth, gas-charged sediment (Acoustic Blanking Layer) masks the remaining internal structure. Fields of two-dimensional megaripples of fine sand (Acoustic Facies 6) show that the modern inner-shelf sand is actively affected by storms.